A formal analysis of lip-pointing in Latin-American Spanish - Ivan Ortega-Santos (Universitat Autònoma de Barcelona, 2016)
The present research focuses on the understudied interface between syntax and gesture within the emerging field of the dialectal syntax of Spanish.  In particular, a formal analysis of so-called lip-pointing in various Latin-American varieties of Spanish is developed. Evidence is provided for the availability of deictic adverbs realized as pointing gestures and, most importantly, gestural pronominals, that is to say, gestures which fulfill a nominal function. The discussion provides evidence for Jouitteau’s (2004, 2007) multi-channeled syntax hypothesis, which states that even in oral languages the externalization procedure may include a gestural component as part of their syntax.